Bibliometric Analysis of Value-Based Marketing - Loso Judijanto (Westscience Press, 2026)
The aim of this paper is to conduct bibliometric analysis of value-based marketing studies and to identify patterns of their intellectual structure, research tendencies, and scientific collaboration by applying the approach of network analysis of publications found in Scopus. Bibliometric methods were used for analyzing the co-occurrence of keywords, author co-citations, institutional collaboration, country collaboration, citation impact, and topic evolution. The results demonstrate that the research in value-based marketing mostly relates to two major directions: customer-centered marketing and value assessment in healthcare. The results of the co-occurrence of keywords suggest that the major keywords include marketing, customer value, sales, commerce, value-based pricing, drug marketing, and cost-effectiveness analysis. The overlay network analysis proves the transition from classical topics like customer value and marketing strategies to new topics of health care economics, value-based pricing, reimbursement policies, and decision-making based on outcomes. Finally, density analysis also confirms the most studied topics to be marketing, sales, drug marketing, and drug costs. Collaborations demonstrate that the US remains the leading country in terms of international cooperation, while European and Asian countries contribute to the development of value-based marketing. Citation analysis highlights influential studies focusing on perceived value, digital marketing, customer engagement, relationship marketing, and value-based differentiation.